Turning peptides in comb silicone polymers§. (16th February 2015) - Jebors, Said; Pinese, Coline; Nottelet, Benjamin; Parra, Karine; Amblard, Muriel; Mehdi, Ahmad; Martinez, Jean; Subra, Gilles
<x xml:space="preserve">Abstract</x> We have recently reported on a new class of silicone–peptide‵ biopolymers obtained by polymerization of di‐functionalized chlorodimethylsilyl hybrid peptides. Herein, we describe a related strategy based on dichloromethylsilane‐derived peptides, which yield novel polymers with a polysiloxane backbone, comparable with a silicone‐bearing pendent peptide chains. Interestingly, polymerization is chemoselective toward amino acids side‐chains and proceeds in a single step in very mild conditions (neutral pH, water, and room temperature). As potential application, a cationic sequence was polymerized and used for antibacterial coating. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.